2019
DOI: 10.1101/517573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The client-binding domain of the cochaperone Sgt2 has a helical-hand structure that binds a short hydrophobic helix

Abstract: The correct targeting and insertion of tail-anchored (TA) integral membrane proteins (IMP) is critical for cellular homeostasis. The mammalian protein SGTA, and its fungal homolog Sgt2 (Sgt2/A), binds hydrophobic clients and is the entry point for targeting of ER-bound TA IMPs. Here we reveal molecular details that underlie the mechanism of Sgt2/A binding to TA clients. We establish that the Sgt2/A C-terminal region is conserved but flexible, sufficient for client binding, and has functional and structural sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 90 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…It is worth noting that low resolution structural studies have suggested that dimeric Sgt2 and HIP position their STI1-domains on opposite ends of a dimer molecule in the absence of client. 22,83 Still, given the noted flexibility in these proteins, 2,20 the possibility of cooperation remains, with the molecular details an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that low resolution structural studies have suggested that dimeric Sgt2 and HIP position their STI1-domains on opposite ends of a dimer molecule in the absence of client. 22,83 Still, given the noted flexibility in these proteins, 2,20 the possibility of cooperation remains, with the molecular details an open question.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] For the mammalian SGTA and its homologs, including yeast Sgt2, the STI1-domain directly binds to clients. 20 SGTA homologs play a number of roles, with the best characterized involving the targeting of tailanchored (TA) proteins to the ER membrane as a member of the Guided Entry of TA protein (GET) pathway. [21][22][23][24][25] SGTA has been suggested to play a role in the degradation of mislocalized membrane proteins in conjunction with the protein Bag6.…”
Section: Introductionmentioning
confidence: 99%
“…Despite similar hydrophobicity thresholds of yeast Sgt2 and Get3, faster binding kinetics were assumed to increase the efficiency of Sgt2 in the rejection of unsuitable cargo [ 152 , 156 , 196 ]. Looking for features in yeast TMHs that allow better discrimination between different TA proteins, it was recently revealed that a so-called hydrophobic helical face geometry (the clustering of hydrophobic residues on one side of a TMH) was more successful in predicting the destined organelle than the overall hydrophobicity [ 205 ]. Strikingly, the finding was reflected by the results of a modeled structure and the binding behavior of yeast Sgt2.…”
Section: Multifactorial Polypeptide Targeting Pathways: the Srp Get And Snd Systemsmentioning
confidence: 99%
“…How the binding and release of cargo is regulated without nucleotide binding and hydrolysis has yet to be determined. Recent computational modeling supported by biochemical data identified a similar hand structure for the binding of at least 11 residues, preferably containing clusters of leucine residues [ 205 , 208 ]. Since a typical TA-TMH has 18–20 amino acids, it was speculated that the two C-termini in a SGTA homodimer may occupy the full length of the signal, similar to the binding mode of calmodulin.…”
Section: Multifactorial Polypeptide Targeting Pathways: the Srp Get And Snd Systemsmentioning
confidence: 99%
See 1 more Smart Citation